The Factors Affecting Trajectory Profile of BCP-A2 Offshore Jacket During Launching Front A Transhortation Barge - Aini Zaliha Alias, Aini Zaliha (Universiti Teknologi Petronas, 2009)
Jacket structures are commonly used in shallow water regions. A jacket can be installed by lifting or launching from a barge into the water. As the jacket becomes heavierin its own weight,launching technique is preferred;economically. However in the other hand the procedure is too risky for the jacket 's design life. The purpose of this studs is to investigate optimum condition during launch based on tarjector analysis result and to obtain main parameter that affect the jacket during, launch from barge